Aktivasi Keterlibatan Publik dalam Program Berita ‘NET 10’ - Anggraeni, Dinar Safa; Karlinah, Siti; Yudhapramesti, Pandan (ARISTO, 2017)
This research entitled Activation of The Public Engagement in `NET 10` News Program. An intrinsic case study by Robert E. Stake on Activating The Public Engagement in `NET 10` Citizen Journalism NET TV’s News Program. This research aimed to understand NET TV’s public management strategy in 'NET 10' news program. In addition, this research also aimed to determine how the editorial staff considere the standard of news value and news judgment on citizen journalist news, and the function of public sphere in the mass media of citizen journalism. The method used qualitative research with intrinsic case study approach by Robert E. Stake to NET TV’s editorial. The results showed the editorial’s strategy of public management by following action: (1) provided easily of joining  'NET CJ', (2) created  campaigns to increase the number of CJ, (3) nature CJ by keeping good and giving relationship evaluations, (4) provides rewards for the creator of CJ news aired in 'NET 10', and (5) educates CJ in making a citizen journalism news. NET TV used curation techniques in the process of citizen journalism news gatekeeper to keep the news value and news judment standard of citizen journalism news. Unfortunately, ‘NET 10’’s citizen journalism news rate of the proportion of news comprehensive continues to fall down because the editorial put loyalty forward. 'NET CJ' act as a opinions catalyst of the citizens to the government.